2014
DOI: 10.1371/journal.pone.0106682
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics-Mediated Identification of Fer Kinase as a Target of Mutant Shp2 in Noonan and LEOPARD Syndrome

Abstract: Noonan syndrome (NS) and LEOPARD syndrome (LS) cause congenital afflictions such as short stature, hypertelorism and heart defects. More than 50% of NS and almost all of LS cases are caused by activating and inactivating mutations of the phosphatase Shp2, respectively. How these biochemically opposing mutations lead to similar clinical outcomes is not clear. Using zebrafish models of NS and LS and mass spectrometry-based phosphotyrosine proteomics, we identified a down-regulated peptide of Fer kinase in both N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
4
8
0
Order By: Relevance
“…We generated gene specific probes to fer cDNA for in situ hybridization, to determine the spatio-temporal expression during development. Similar to what was reported by Paardekooper Overman et al [ 20 ], we found fer to be expressed ubiquitously until approximately ten somites, when it became more specifically concentrated toward the head region. However, we also observed fer expression in the primordial region of the dorsal aorta (DA)/cardinal vein (CV), when compared to a fer antisense probe negative control (In Figure 1 B,C, respectively—24 hpf is shown).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…We generated gene specific probes to fer cDNA for in situ hybridization, to determine the spatio-temporal expression during development. Similar to what was reported by Paardekooper Overman et al [ 20 ], we found fer to be expressed ubiquitously until approximately ten somites, when it became more specifically concentrated toward the head region. However, we also observed fer expression in the primordial region of the dorsal aorta (DA)/cardinal vein (CV), when compared to a fer antisense probe negative control (In Figure 1 B,C, respectively—24 hpf is shown).…”
Section: Resultssupporting
confidence: 91%
“…Improper splicing with the fer MO was confirmed using PCR to amplify the region spanning exon 9, using a forward primer in exon 8 (5′-AGTCCACCACAGAGGAGCTG-3′) and a reverse primer in exon 10 (5′-AGTCTGTCCTTGGCTCTTCG-3′) (Figure 2I). Although not shown here, experiments repeated with MOs and PCR primers, as reported by Paardekooper Overman, et al (P-O MO), confirmed specificities for the Fer gene were consistent with data obtained using our fer -MO1 (Fer protein knockdown with both MOs is shown in Supplementary Figure S1 as fer -MO1 and P-O MO) [ 20 ]. Morpholino knockdown was confirmed using a Western blot analysis, using an anti-Fer monoclonal antibody (Cell Signaling).…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations